2020
DOI: 10.3390/nu12103081
|View full text |Cite
|
Sign up to set email alerts
|

Brief Hospital Supervision of Exercise and Diet During Adjuvant Breast Cancer Therapy Is Not Enough to Relieve Fatigue: A Multicenter Randomized Controlled Trial

Abstract: Supervised exercise dietary programs are recommended to relieve cancer-related fatigue and weight increase induced by adjuvant treatment of early breast cancer (EBC). As this recommendation lacks a high level of evidence, we designed a multicenter randomized trial to evaluate the impact of an Adapted Physical Activity Diet (APAD) education program on fatigue. We randomized 360 women with EBC who were receiving adjuvant chemotherapy and radiotherapy to APAD or usual care at eight French cancer institutions. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 55 publications
0
50
0
Order By: Relevance
“…After 171 duplicates had been removed, titles and abstracts from the remaining 919 records were screened and the full text of 568 was assessed for eligibility. Finally, 13 studies were included in this systematic review describing 12 interventions [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] (i.e., one intervention published 2 studies showing its results). We were forced to discard one study conducted by Arikawa et al [ 38 ] because the p-values were not reported, even though some variable changes, body mass and fitness level, were listed as significant in the body of the article.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After 171 duplicates had been removed, titles and abstracts from the remaining 919 records were screened and the full text of 568 was assessed for eligibility. Finally, 13 studies were included in this systematic review describing 12 interventions [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] (i.e., one intervention published 2 studies showing its results). We were forced to discard one study conducted by Arikawa et al [ 38 ] because the p-values were not reported, even though some variable changes, body mass and fitness level, were listed as significant in the body of the article.…”
Section: Resultsmentioning
confidence: 99%
“…The average age of patients ranged from 49.0 [ 30 , 31 ] to 58.7 years [ 37 ]. Eight interventions included patients receiving exercise plus diet interventions [ 26 , 27 , 28 , 30 , 31 , 33 , 34 , 35 , 36 ], and four interventions included patients receiving exercise plus supplementation interventions [ 25 , 29 , 32 , 37 ]. Of the 12 interventions analysed, in 11 of them, participants had a body mass index (BMI) > 25 kg/m 2 [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to a supervised exercise programme, home-based exercise also showed promising prospects in cancer rehabilitation. A multicentre randomized controlled trial suggested that home-based physical activity consisted of combined endurance (same as aerobic exercise) and resistance training during 27 weeks significantly increased VO 2 peak compared to a decrease in the usual care group [17]. In addition to endurance and resistance exercise, home-based walking training was also reported to benefit breast cancer patients for cardiorespiratory fitness [18].…”
Section: Rehabilitation In Cancer Survivorsmentioning
confidence: 99%